Biochar from pyrolysis of cellulose: An alternative catalyst support for the electro-oxidation of methanol. (6th July 2016) - Nieva Lobos, María Luz; Sieben, Juan Manuel; Comignani, Vanina; Duarte, Marta; Volpe, María Alicia; Moyano, Elizabeth Laura
Abstract: In the present study, the biochar produced by fast pyrolysis at 350 °C of untreated and acid-treated cellulose are evaluated as supports of CuRu@Pt core-shell nanoparticles (2.9–3.5 nm) for the electro-oxidation of methanol in acid media. Carbon materials and the supported core-shell nanoparticles were characterized by physicochemical and electrochemical techniques. Cyclic voltammetry and chronoamperometry were used to study the activity of the catalysts. The nanocatalyst supported onto the biochar from acid-treated cellulose exhibited high electroactive surface area (38 m 2 /g) and high performance in the methanol electro-oxidation reaction, reaching TON values of 0.151 molec. (sites s) −1 at 0.5 V. This contribution provides a new approach for the utilization of an inexpensive carbon material precursor as cellulose to design alternative catalytic systems and their emerging applications in electrocatalysis. Highlights: Biochar from cellulose is used as a carbon support of CuRu@Pt core-shell nanoparticles. Nanocatalyst supported onto the cellulose biochar is efficient in the methanol electro-oxidation. Acid-treated cellulose derived biochar shows better performance than activated carbon.